2011
DOI: 10.1007/s13197-011-0602-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of frying conditions on the physico-chemical properties of rice bran oil and its blended oil

Abstract: The changes occurring in rice bran oil and its blend with sunflower oil during repeated frying cycles of dried and moist potato chips were monitored. The parameters assessed were: Colour, Refractive Index, SpecificGravity, Oryzanol Value, Free fatty acid, Iodine Value, Peroxide value, anisidine value, Saponification Value, trans fats and fatty acid composition. No significant changes (p≤0.05) were observed in the refractive index and specific gravity of rice bran oil, sunflower oil and their model blend. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 7 publications
3
29
0
Order By: Relevance
“…Table 4 shows fat content of fried chicken chops as a function of frying method and time. In previously published studies (Koh et al, 2011;Debnath et al, 2012;Mishra & Sharma, 2014), it was noted that the frying time had remarkable influence on oil content of fried products. This was also observed in the present study, where oil content showed significant (p<0.05) increment in the last day and in the last three days in the case of DWF and PDF, respectively.…”
Section: Cie Color Valuesmentioning
confidence: 99%
“…Table 4 shows fat content of fried chicken chops as a function of frying method and time. In previously published studies (Koh et al, 2011;Debnath et al, 2012;Mishra & Sharma, 2014), it was noted that the frying time had remarkable influence on oil content of fried products. This was also observed in the present study, where oil content showed significant (p<0.05) increment in the last day and in the last three days in the case of DWF and PDF, respectively.…”
Section: Cie Color Valuesmentioning
confidence: 99%
“…3,[44][45][46] Edible oils, including RBO, are characterized by their major and minor components. Crude RBO is composed of 4% unsaponifiable matter, such as tocopherols and tocotrienols; 2-4% free fatty acids (FFAs) at the time of milling; and 88-89% triacylglycerols (neutral lipids).…”
Section: Physicochemical Properties Of Rice Bran Oilmentioning
confidence: 99%
“…This observation provides information of gradual cis to trans isomerization throughout this treatment process (Sanahuja et al 2009;Tena et al 2009). Moreover, Mishra and Sharma (2011) reported that repeated frying caused trans fatty acids to increase while the blended samples were within the acceptable range after few frying cycles. In this case, palm olein has the lowest absorption band (0.220) as well, where as Soybean oil shows the highest with 0.265 followed by sunflower and canola oil at (0.244 and 0.238, respectively) but candlenut oil does not give any band at this frequency.…”
Section: Ftir Analysismentioning
confidence: 99%